Unusual C,O-fused glycosylapigenins from serjania marginata leaves - Heredia-Vieira, Silvia C. [UNESP]; Simonet, Ana M.; Vilegas, Wagner [UNESP]; Macias, Francisco A. (Amer Chemical Soc, 2015)
A phytochemical study of a Serjania marginata leaf extract with antiulcer activity afforded 15 compounds, including the new 3-O-alpha-L-arabinopyranosyl(1 -> 3)-alpha-L-rhamnopyranosyl(1 -> 2)[beta-D-glucopyranosyl(1 -> 4)]-alpha-L-arabinopyranosyloleanolic acid (1) and 7,5 "-anhydroapigenin 8-C-alpha-(2,6-dideoxy-5-hydroxy-ribo-hexopyranosyl)-4'-O-beta-D-glucopyranoside (4). The structures of the new compounds were determined by spectroscopic analysis, including 1D and 2D NMR techniques, mass spectrometry, and chemical methods. Compound 4 is a C-hexopyranosylapigenin with an unusual cyclic ether linkage between C-5" and C-7 of apigenin. The isolated proanthocyanidins have high antioxidant activities, and these compounds are probably responsible for the gastroprotective effect of the extract.